2009
DOI: 10.1089/jop.2008.0107
|View full text |Cite
|
Sign up to set email alerts
|

Eyedrops Containing SA9000 Prodrugs Result in Sustained Reductions in Intraocular Pressure in Rabbits

Abstract: Aim: Poor topical bioavailability and ocular irritation have impeded the development of the diuretic, ethacrynic acid (ECA) as a clinically useful ocular hypotensive for the treatment of glaucoma. Thus, the development of analogs and prodrugs of analogs with improved ocular penetration, potency, and tolerability is required. The aim of this work is to evaluate the corneal penetration and ocular distribution of SA9000, an ECA analog. Novel SA9000 prodrugs intended to further improve ocular pharmacodynamic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Digoxin has antiarrhythmic effects via myocytes and some older literature sources describe the lowering effect of digoxin on the IOP in human [ 28 - 30 ] and cats [ 31 ], probably due to blocking of Na + /K + -ATPase in the CBE. Ethacrynic is a diuretic drug and multiple animal studies already showed the IOP lowering effect of intracameral or topical administered ethacrynic acid in the eye, probably through increased AH outflow, but possibly also by decreased AH production [ 32 - 39 ]. The major disadvantage of athacrynic acid is the risk for (severe) corneal edema.…”
Section: Discussionmentioning
confidence: 99%
“…Digoxin has antiarrhythmic effects via myocytes and some older literature sources describe the lowering effect of digoxin on the IOP in human [ 28 - 30 ] and cats [ 31 ], probably due to blocking of Na + /K + -ATPase in the CBE. Ethacrynic is a diuretic drug and multiple animal studies already showed the IOP lowering effect of intracameral or topical administered ethacrynic acid in the eye, probably through increased AH outflow, but possibly also by decreased AH production [ 32 - 39 ]. The major disadvantage of athacrynic acid is the risk for (severe) corneal edema.…”
Section: Discussionmentioning
confidence: 99%
“…So, in 1993, I thought I had cured trabecular glaucoma!!!!! Unfortunately, the subsequent decade proved that ECA was very difficult to deliver topically into the eye and, despite many attempts 19,23,24 (still ongoing!) neither ECA nor its direct analogues have proven to be a suitable topical glaucoma drug.…”
Section: Passion For Focus On Trabecular Meshwork/ Glaucoma Science Amentioning
confidence: 99%
“…Other options to avoid multiple applications include the use of combinations of already commercialized hypotensive agents [17][18][19][20] or the search for novel active substances with high ocular hypotensive efficacy and low adverse effects on the eye. [21][22][23][24] In addition, several strategies have been developed to increase the bioavailability of topical antiglaucoma drugs by prolonging the contact time of the drug on the ocular surface. [25][26][27] Cellulose polymers are very popular and are used for artificial tear solutions and as enhancers of ophthalmic vehicles' viscosity, in a manner that reduces the drainage rate of the drug from the eye and subsequently improves the therapeutic efficacy.…”
mentioning
confidence: 99%